Influence Of Taxation Socialization, Tax Sanctions, Tax Knowledge On Individual Taxpayer Compliance (At The Bandung Soreang Primary Tax Office) - Putra, Raihan Cipta Permana; Ginting, Wajib (International Journal of Marketing & Human Resource Research, 2025)
This study analyzes the effect of tax socialization, tax sanctions, and tax knowledge on individual taxpayers' compliance at the Soreang Tax Office (KPP Pratama Soreang). Taxpayer compliance is one of the most crucial indicators of the success of Indonesia's tax system. The causes of non-compliance with tax obligations often stem from factors such as a lack of public understanding of their tax responsibilities, insufficient socialization, and inconsistent enforcement of tax sanctions. This study employs a quantitative method, including descriptive and confirmatory measurements. Data was collected by surveying 100 taxpayers at the Soreang Tax Office. The findings reveal that tax socialization positively and significantly impacts taxpayer compliance by giving individuals a stronger understanding of their tax obligations. Tax sanctions also play a significant role, with compliance improving through the consistent application of sanctions. Tax knowledge is a critical factor, as informed taxpayers tend to comply with reporting requirements more promptly. Together, these three variables significantly contribute to enhancing compliance. These findings underscore the importance of expanding tax socialization programs, implementing tax regulations effectively, and educating the public about tax matters to support the success of Indonesia's tax system